Un scrutin pour trois pays : la nouvelle géographie politique italienne suite à l’élection législative du 4 mars 2018 - Matteo Cavallaro; Davide Policastro; Guido Salza; Massimo Angelo Zanetti (EchoGéo)
In this article we describe and analyse the results of the Italian General Election of March 4, 2018. In particular, we focus on the geographical differences in the scores distribution of the main political forces. We argue that, from this point of view, Italy appears as a tripolar-but-imperfect political system with two major poles (centre-right and M5S) and a non-competitive pole, the centre-left. We then observe the relationship between the distribution of electoral preferences and the distribution of a series of socio-demographic variables, in order to identify the main elements describing these “three Italies”: (i) the country of the small northern cities, with leghista hegemony, (ii) an Italy made of large and well-educated urban areas, which votes for the centre-left, and finally (iii) the poor regions of the South, newly acquired areas for the M5S.